High school students’ achievement goal adoption: Evidence from neglected rural high schools in Iran - Mohammad Sajedifard; Zahra Sajedifard (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The study aimed to examine rural high schoolers’ achievement goal preferences and the potential gender variations in a neglected rural context in Iran. To this end, a sample of 252 high schoolers answered Elliott and Murayama’s (2008) Achievement Goal Questionnaire-Revised (AGQ-R). Quantitative results indicated the prevalence of mastery approach (MAp) and performance approach (PAp) goals, followed by performance avoidance (PAv) and mastery avoidance (MAv) goals. Further, an examination of gender differences indicated no significant differences between male and female high schoolers in their adoption of MAp, PAp and MAv goals. However, a significant difference was observed between male and female students in their resort to PAv goal. Results may have implications for different individuals in educational settings such as educational authorities, teachers, and counselors as well as researchers.